Ex Vivo Human Placental Transfer of Anti-Human Immunodeficiency Virus Compounds - Roger E. Bawdon (Hindawi Limited, 1997)
Objective: The transfer of anti-human immunodeficiency virus (HIV) drugs has been studied in the ex vivo human placental model. There is a paucity of information on the placental transfer of these drugs because of ethical considerations and the expense involved in the use of the non-human primate model.